2005
DOI: 10.1016/j.ydbio.2005.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal pancreas agenesis in retinoic acid-deficient Raldh2 mutant mice

Abstract: During embryogenesis, the pancreas arises from dorsal and ventral pancreatic protrusions from the primitive gut endoderm upon induction by different stimuli from neighboring mesodermal tissues. Recent studies have shown that Retinoic Acid (RA) signaling is essential for the development of the pancreas in non-mammalian vertebrates. To investigate whether RA regulates mouse pancreas development, we have studied the phenotype of mice with a targeted deletion in the retinaldehyde dehydrogenase 2 (Raldh2) gene, enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
188
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(197 citation statements)
references
References 44 publications
8
188
0
1
Order By: Relevance
“…It has been shown that mouse and human ES cells can be efficiently induced into Sox17-positive definitive endoderm by activin A treatment [18][19][20]. RA has been reported to be critical for early pancreas formation during zebrafish and mouse embryonic development [21][22][23][24]. In our study, as shown in Figure 3, when induced by activin A alone, human ES cells weakly express the pancreatic early transcription factors pdx1 and hnf4a.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It has been shown that mouse and human ES cells can be efficiently induced into Sox17-positive definitive endoderm by activin A treatment [18][19][20]. RA has been reported to be critical for early pancreas formation during zebrafish and mouse embryonic development [21][22][23][24]. In our study, as shown in Figure 3, when induced by activin A alone, human ES cells weakly express the pancreatic early transcription factors pdx1 and hnf4a.…”
Section: Discussionsupporting
confidence: 58%
“…The individual effect of activin A and RA on endoderm and pancreas development has also been demonstrated by several other groups [18][19][20][21][22][23][24]. It has been shown that mouse and human ES cells can be efficiently induced into Sox17-positive definitive endoderm by activin A treatment [18][19][20].…”
Section: Discussionmentioning
confidence: 70%
“…Our studies therefore do not address whether this enzymatic activity, especially as it relates to synthesis of retinoic acid, plays an important role in the function of these progenitors, or whether they serve as local sources of retinoic acid production in a manner that organizes surrounding cells. Retinoids have previously been shown to exert profound influences on vertebrate pancreas development (29)(30)(31), and retinoic acid is a critical component for directed differentiation of human ES cells into insulin-producing β-cells (32). In the hematopoietic system, in vitro inhibition of ALDH1 enzymatic activity has been reported to somewhat paradoxically lead to the expansion of undifferentiated hematopoietic progenitors (33), and studies using gene-targeted mice have suggested that Aldh1a1-specific enzymatic activity is dispensable for hematopoietic and neural progenitor cell activity (34).…”
Section: Discussionmentioning
confidence: 99%
“…The level of conservation in determining pancreatic boundary establishment by Cdx4 and Cyp26a1 across vertebrate species has not been determined. In RALDH2 null mice, which lack a critical RA-synthesizing enzyme, the dorsal pancreas fails to bud and the early glucagon þ cells do not develop (Molotkov et al, 2005;Martin et al, 2005). This dorsal pancreas agenesis phenotype in RALDH2 null mice is reminiscent of the pancreas phenotype observed in Islet1 (Isl1) or N-cadherin (Esni et al, 2001) knockout mice.…”
Section: Figmentioning
confidence: 93%